Criminological Analysis of Money Laundering Offenders: A Study of Decision No. 365/Pid.Sus/2023/PN JKT.Tim - Friska Julita Marbun; Immanuel Simanjuntak; Syabrina Febriyani (JURNAL MERCATORIA, 2026)
This study aims to analyze the criminological characteristics of offenders involved in money laundering derived from fraud and to critically examine the judicial reasoning in Decision Number 365/Pid.Sus/2023/PN JKT.Tim. The study focuses on the increasing use of fraud schemes, particularly romance scams and fictitious investments, as predicate offenses for money laundering conducted through electronic financial transactions. This research employs a normative legal method using statutory regulations, court decisions, and relevant legal and criminological literature, with data analyzed qualitatively through Rational Choice Theory and Routine Activity Theory. The results indicate that the offender acted through rational and planned decision-making aimed at obtaining economic benefits by means of deception, coordination with other actors, and the use of multiple financial accounts. The findings also reveal characteristics of network-based criminal activity involving role differentiation among offenders. Furthermore, the study identifies several issues in the court's reasoning, particularly regarding the assessment of the defendant's role within the criminal scheme, the interpretation of knowledge and intent in money laundering offenses, and the proportionality of the sentence imposed in relation to the harm suffered by the victim. Therefore, the significance of this study lies not merely in confirming the fulfillment of the legal elements of money laundering but in critically examining how offender responsibility and punishment are assessed in complex financial crimes involving multiple actors.